Mitigate lumbar crash injury of reclined occupants with assisted repositioning device - Shen, Wenxuan; Zhou, Qing (Frontiers in Bioengineering and Biotechnology, 2025)
In autonomous vehicles, reclined seating positions are increasingly popular for improving occupant comfort, but they also pose significant challenges for crash safety, especially concerning lumbar injury risks. This study investigated the potential of assisted repositioning to mitigate lumbar injuries in reclined occupants during frontal collisions. Assisted repositioning combined active intervention with collision inertia to return reclined occupants to an upright posture prior to peak lumbar loads. THUMS simulations at crash severities from 30 km/h to 70 km/h demonstrated that assisted repositioning could significantly reduce lumbar injury risk, particularly at 50 km/h, where the risk decreased from 66.9% to 32.4%. To provide whole-body protection, this study introduced two solutions for coordinating repositioning devices with the conventional three-point seatbelt. The “active solution” utilized an active lumbar support for repositioning, while the “passive solution” employed a lumbar airbag. Both solutions emphasized the need for careful coordination of occupant repositioning with seatbelt functions to optimize safety across different body regions. These findings presented a new strategy for enhancing crash protection in flexible cabin configurations, contributing to occupant safety in future autonomous vehicles.